IMPLEMENTASI WAKAF ISTIBDAL DALAM PEMBEBASAN LAHAN PEMBANGUNAN JALAN TOL (Studi Kasus Pembangunan Jalan Tol Surabaya-Mojokerto) - Fikri Ariza Achmad; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The background of this research is the existence of massive infrastructure development by the government, one of which is the construction of the Surabaya-Mojokerto Toll Road. The construction process of the Surabaya-Mojokerto Toll Road passes through the land and buildings owned by residents, and including to waqf land. One of the waqf land affected by the construction process of the Surabaya-Mojokerto Toll Road is the Sabilun Najah Mosque. This phenomenon encourages researchers to raise research that discusses how the waqf istibdal process, both in terms of changes in waqf assets and in the administration process of licensing. This study uses a qualitative approach with a case study strategy. Data collection is done through interview techniques with relevant parties and related documents. The data analysis technique used is making explanations. The results of this study indicate that the process of changing the waqf assets of the Sabilun Najah Mosque runs in accordance with statutory procedures. The waqf istibdal process consists of the process of changing the waqf property and the licensing administrative process. The process of changing waqf property consists of planning, implementation, coordination between toll management and nazir, searching for replacement land, replacing land replacement processes, and the process of building a new mosque. The second process consists of a licensing process that starts from nazir, the Office of the Ministry of Religion Sidoarjo Regency, and the Regional Office of the Ministry of Religion of East Java.Keywords: implementation, waqf, waqf istibdal, mosque, land acquisition, toll road, Surabaya-Mojokerto Toll RoadREFFERENCESAlquran Kementerian Agama RepublikIndonesiaDirektorat Pemberdayaan Wakaf DirektoratJenderal Bimbingan Masyarakat IslamDepartemen Agama. Fiqih Wakaf.Direktorat Pemberdayaan Wakaf. 2007.Paradigma Baru Wakaf di Indonesia,Cet 1. Jakarta: Dirjen Bimas IslamDirektorat Pengembangan Zakat dan Wakaf.2005. Wakaf Tunai dalam PerspektifHukum Islam. Jakarta: TPHalim, Abdul. M.A. 2005. Hukum Perwakafandi Indonesia. Jakarta: Ciputat Press.Kahf, Monzer. 2006. al-Waqf al-IslamiTaṣawwuruhu, Idaratuhu,Tanmiyatuhu. Damaskus: Dar al-FikrKarim, Shamsiah Bte Abdul. 2010.Contemporary of Shari’a ComplianceStructuring for the Development andManagement of Waqf Asset inAchmad, et al/Jurnal Ekonomi Syariah Teori dan Terapan Vol. 6 No. 9 September 2019: 1924-1935;IMPLEMENTASI WAKAF ISTIBDAL DALAM PEMBEBASAN LAHAN PEMBANGUNAN JALAN TOL (STUDIKASUS PEMBANGUNAN JALAN TOL SURABAYA-MOJOKERTO)10Singapore. Kyoto Bulletin of IslamicArea Studies pp. 143–164.Mugniyah, Muhammad Jawad. 2010. FiqhLima Madzhab: Ja’fari, Hanafi, Syafi’i,Hambali. Jakarta: Lentera.Mukhlisin, Muzarie. 2010. Hukum Perwakafandan Implikasinya TerhadapKesejateraan Umat (ImplementasiWakaf di Pondok Modern DarussalamGontor) cet 1. Jakarta: KementerianAgamaPeraturan Pemerintah Nomor 42 Tahun 2006tentang Pelaksanaan Undang-UndangNomor 41 Tahun 2004 tentang Wakafdan Kompilasi Hukum IslamPeraturan Pemerintah Republik Indonesia No.8 Tahun 1990 Tentang Jalan TolPeraturan Pemerintah Republik IndonesiaNomor 25 Tahun 2018 tentangPerubahan Atas PeraturanPemerintah Nomor 42 Tahun 2006Tentang Pelaksanaan Undang-Undang Nomor 41 Tahun 2004Tentang Wakaf Dalam Undang-Undang Nomor 41 Tahun 2004tentang WakafSugiyono. 2012. Metode Penelitian KuantitatifKualitatif dan R&D. Bandung:Alfabeta.Undang-Undang Nomor 26 Tahun 2007Tentang Penataan Ruang.Undang-Undang Nomor 41 Tahun 2004tentang WakafWirartha, I Made. 2006. Metodologi PenetilianSosial Ekonomi. Yogyakarta: CV AndiOffset.Yin, Robert. K. 2009. Studi Kasus; Desain danMetode. Jakarta: Raja GrafindoPersada.bpjt.pu.go.id/ (laman Badan Pengatur JalanTol)www.jasamarga.com (laman Jasa Marga)https://bwi.or.id/ (laman Badan WakafIndonesia)https://katadata.co.id/ (laman perusahaanmedia dan riset berita ekonomi danbisnis)https://www.kpu.go.id/ (laman KomisiPemilihan Umum Republik Indonesia)